Cultural standards of Bosnia and Herzegovina: Empirical findings and implications for strategic human resource management - Christian Hirt; Renate Ortlieb (Journal for East European Management Studies, 2012)
According to theoretical approaches to strategic human resource management (SHRM), knowledge about a country's business culture and the ability to develop appropriate skills are a source of competitive advantage. This article analyses cultural standards in the transition economy of Bosnia and Herzegovina. On the basis of narrative interviews with twelve Austrian managers and feedback sessions with thirty Bosnian business experts we identify seven cultural standards, for example regarding bureaucratic behaviour, decision making and customer focus. Therewith we contribute to culture specific human resource management (HRM) research and deficient cross-cultural literature for transition economies. – – Theoretischen Ansätzen des strategischen Personalmanagements zufolge können Wissen über eine landesspezifische Geschäftskultur und die Fähigkeit entsprechende Kompetenzen zu entwickeln, einen strategischen Wettbewerbsvorteil begründen. Dieser Artikel analysiert Kulturstandards in Bosnien und Herzegowina. Auf der Basis von narrativen Interviews mit zwölf österreichischen Managern und Feedbacksessions mit dreißig bosnischen Managern identifizieren wir sieben Kulturstandards. Diese beziehen sich zum Beispiel auf bürokratisches Verhalten, Entscheidungsverhalten und Kundenorientierung. Damit leisten wir einen Beitrag zur kaum beachteten länderbezogenen Personal- und Kulturforschung in Transformationsländern.
Keywords: 650; Strategic human resource management; cross-cultural management; cultural standards; cultural standard method; strategic training; South Eastern Europe